ASA Physical Status Classification and Complications Following Facial Fracture Repair. (November 2022) - Thepmankorn, Parisorn; Choi, Chris B.; Haimowitz, Sean Z.; Parray, Aksha; Grube, Jordon G.; Fang, Christina H.; Baredes, Soly; Eloy, Jean Anderson
Background: To investigate the association between American Society of Anesthesiologists (ASA) physical status classification and rates of postoperative complications in patients undergoing facial fracture repair. Methods: Patients were divided into 2 cohorts based on the ASA classification system: Class I/II and Class III/IV. Chi-square and Fisher's exact tests were used for univariate analyses. Multivariate logistic regressions were used to assess the independent associations of covariates on postoperative complication rates. Results: A total of 3575 patients who underwent facial fracture repair with known ASA classification were identified. Class III/IV patients had higher rates of deep surgical site infection ( P = .012) as well as bleeding, readmission, reoperation, surgical, medical, and overall postoperative complications ( P < .001). Multivariate regression analysis found that Class III/IV was significantly associated with increased length of stay ( P < .001) and risk of overall complications ( P = .032). Specifically, ASA Class III/IV was associated with increased rates of deep surgical site infection ( P = .049), postoperative bleeding ( P = .036), and failure to wean off ventilator ( P = .027). Conclusions: Higher ASA class is associated with increased length of hospital stay and odds of deep surgical site infection, bleeding, and failure to wean off of ventilator following facial fracture repair. Surgeons should be aware of the increased risk for postoperative complications when performing facial fracture repair in patients with high ASA classification.